Electrodeposited Inconel and Stellite like Coatings for Improved Corrosion Resistance in Biocombustors. (7th July 2017) - Hall, Timothy D; Vijapur, Santosh H.; Taylor, E. J.; Inman, Maria; Brady, Michael
Abstract : Various electroplated coatings from [Ni/Co]-Cr-[Mo/Fe] systems, were tested to assess their potential to enhance lifetime performance of low-cost stainless steels exposed to bio-combustor operating conditions. A wide range of electrodeposition processing conditions and electrolytes were evaluated based upon an ability to: (1) design REACH compliant electrolytes that enable a wide range of potentially corrosion resistant alloys to be electrodeposited; (2) scale the process to enable compositionally and structurally uniform coatings to be formed onto SS test pieces; and (3) maintain coating adherence and corrosion resistance during accelerated high temperature corrosion studies. Within this program we developed uniform, dense, well-adhered alloy coatings of various compositions, and performed accelerated high temperature corrosion studies to ascertain which alloys maintained better substrate adherence and corrosion resistance when exposed to salted thermal exposure conditions of 700ºC for 500 h.